UTILIZATION OF HINDU RELIGIOUS CEREMONIAL GARBAGE IN BALI AS FABRIC DYE - Ni Made Santi Udiyani; Ni Kadek Yuni Diantari; Putu Ari Darmastuti (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
This study aims to determine the ceremonial waste of the Hindu community in Bali which can be used as an environmentally friendly textile dye. In carrying out religious ceremonies, the Hindu community in Bali makes offerings such as offerings that cannot be utilized optimally after the ceremony takes place so most of it becomes organic waste. In this study, the waste of Hindu ceremonies in Bali in the form of organic waste will be tested to produce a solution of natural dyes using a pre-experimental method. The pre-experimental method explores the extraction technique of several samples of organic waste with water as a solvent on textile materials, namely cotton cloth. The process of making this natural dye solution goes through three main processes, namely pre-mordant, extraction of dye raw materials, and fixation. Some samples of organic waste found in Hindu religious ceremonies in Bali have plant color pigments such as balsamina purple, red, hydrangea, marigold, pandan leaves, shallot skin, turmeric, and areca nut was extracted to produce a natural color solution. The extraction of the color solution is able to bring out several color tones on textile materials, namely cotton fabrics. Through this research, it is hoped that it can be one of the people’s choices in producing natural color as textile materials that can be produced simply as well as an effort to reduce organic waste produced in Hindu community ceremonies in Bali.